Human papilloma virus in oral cancer - Kim, Soung Min (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2016)
Cervical cancer is the second most prevalent cancer among women, and it arises from cells that originate in the cervix uteri. Among several causes of cervical malignancies, infection with some types of human papilloma virus (HPV) is well known to be the greatest cervical cancer risk factor. Over 150 subtypes of HPV have been identified; more than 40 types of HPVs are typically transmitted through sexual contact and infect the anogenital region and oral cavity. The recently introduced vaccine for HPV infection is effective against certain subtypes of HPV that are associated with cervical cancer, genital warts, and some less common cancers, including oropharyngeal cancer. Two HPV vaccines, quadrivalent and bivalent types that use virus-like particles (VLPs), are currently used in the medical commercial market. While the value of HPV vaccination for oral cancer prevention is still controversial, some evidence supports the possibility that HPV vaccination may be effective in reducing the incidence of oral cancer. This paper reviews HPV-related pathogenesis in cancer, covering HPV structure and classification, trends in worldwide applications of HPV vaccines, effectiveness and complications of HPV vaccination, and the relationship of HPV with oral cancer prevalence.